Comparative Analysis Of Cost And Time In The Implementation Of Rigid And Flexible Pavement: A Case Study Of The Sambeng–Kedewan Road Section, Bojonegoro District - Abid, Ahmad Rois; Tjendani, Hanie Teki; Putri, Erni Puspanantasari (Asian Journal of Social and Humanities, 2025)
The development of transportation infrastructure plays a pivotal role in supporting regional economic growth, particularly in areas undergoing rapid industrial and residential expansion. This study aims to conduct a comparative analysis between rigid pavement (concrete) and flexible pavement (asphalt) in terms of cost efficiency and implementation time on the Kedamean Sidoraharjo Randegan road section in Gresik Regency, East Java. The region’s strategic position, reinforced by the operation of the Krian Legundi Bunder Manyar (KLBM) toll road, has significantly increased traffic flow, thereby creating an urgent need for durable and sustainable road infrastructure. This research employs a quantitative descriptive approach by integrating traffic projections (Average Daily Traffic or LHR) for the 20th and 40th year horizons, CESAL calculations (Cumulative Equivalent Standard Axle Load), and pavement structure design using the MDPJ 2017 method for flexible pavement and Pd T-14-2003 for rigid pavement. Additionally, cost estimations are based on regional unit prices issued by the Gresik Regency Public Works Department. Findings indicate that although flexible pavement offers shorter construction time and lower initial costs, rigid pavement proves more cost-effective in the long run due to its durability and lower maintenance needs. The study also highlights that utilizing existing pavement layers can reduce construction costs by up to 10%, aligning with sustainable infrastructure practices. The results are expected to serve as a practical guideline for civil engineering practitioners and local governments in making strategic decisions regarding pavement type selection based on traffic intensity, budget availability, and long-term development goals.